2019
DOI: 10.1029/2018ja026384
|View full text |Cite
|
Sign up to set email alerts
|

Pitch Angle Scattering of Sub‐MeV Relativistic Electrons by Electromagnetic Ion Cyclotron Waves

Abstract: Electromagnetic ion cyclotron (EMIC) waves have long been considered to be a significant loss mechanism for relativistic electrons. This has most often been attributed to resonant interactions with the highest amplitude waves. But recent observations have suggested that the dominant energy of electrons precipitated to the atmosphere may often be relatively low, less than 1 MeV, whereas the minimum resonant energy of the highest amplitude waves is often greater than 2 MeV. Here we use relativistic electron test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
63
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(65 citation statements)
references
References 56 publications
(134 reference statements)
2
63
0
Order By: Relevance
“…It is important to note that the simulation results without (with) including hot plasma effects due to EMIC waves can only explain the electron precipitation at energies >~800 keV (>~1 MeV), requiring other mechanisms to explain the low energy electron precipitation down to ~250 keV. For example, nonresonant scattering (e.g., Chen et al, ) and nonlinear effects (Denton et al, ; Hendry et al, ; Kubota et al, ; Omura & Zhao, , ) are suggested to lower the E min down to a few 100s keV. However, the evaluation of these effects is beyond the scope of this case study and left as future investigation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…It is important to note that the simulation results without (with) including hot plasma effects due to EMIC waves can only explain the electron precipitation at energies >~800 keV (>~1 MeV), requiring other mechanisms to explain the low energy electron precipitation down to ~250 keV. For example, nonresonant scattering (e.g., Chen et al, ) and nonlinear effects (Denton et al, ; Hendry et al, ; Kubota et al, ; Omura & Zhao, , ) are suggested to lower the E min down to a few 100s keV. However, the evaluation of these effects is beyond the scope of this case study and left as future investigation.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Do EMIC waves only act on ultrarelativistic electrons (cf. Denton et al, , in this collection and discussion in section )? Another question that warrants deeper investigation is whether EMIC scattering occurs significantly or not in the plasmasphere and inner zone.…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 94%
“…These waves drive considerable contemporary scientific interest, particularly during the recent Van Allen Probes mission. Many recent studies are dedicated to the loss they cause to ultrarelativistic electrons (e.g., Thorne & Kennel, ; Albert, ; Jordanova et al, ; Miyoshi et al, ; Rodger et al, , Rodger et al, ; Li et al, , 2014; Usanova et al, , ; Kersten et al, ; Blum et al, ; Clilverd et al, ; Woodger et al, , ; Colpitts et al, ; Shprits et al, , , , ; Hendry et al, , ; Zhang et al, ; Aseev et al, ; Drozdov, Shprits, Usanova, et al, ; Capannolo et al, , ; Denton et al, ; Qin et al, ), themselves related to the complex location and duration of these waves. EMIC waves are discrete electromagnetic emissions in multiple frequency bands (e.g., Saikin et al, ), which are observed across a large region of geospace (e.g., Saikin et al, ), including the ring current and the plasmasphere, dayside plumes, and the outer dayside magnetosphere (Engebretson et al, ; Engebretson et al, ; Engebretson et al, ; Tetrick et al, ).…”
Section: Particle Loss In the Inner And Outer Zonesmentioning
confidence: 99%
See 2 more Smart Citations